Analysis of Factors that Influence the Level of Crime in Indonesia - Marwin Apriza; Bambang Agoes Hermanto (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research aims to find out what factors influenced the increase in Indonesian crime in 2017–2021. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS). The method used in this research is multiple analysis using panel data for 2017–2021. The variables used are unemployment, the GRDP growth rate, poverty, and the Gini ratio. The results of this research show that the unemployment rate, poverty, and income inequality variables have a significant effect on the crime rate, while the GRDP variable does not have a significant effect on the crime rate in Indonesia in 2017–2021.